Fairest. Volume 5, The clamour for glamour - Buckingham, Mark; Willingham, Bill (DC Comics/Vertigo, 2015)
"In this new epic, refugees from Fabletown have returned to New York's Castle Dark, and Reynard, now able to shapeshift from fox to man, travels the mundane world to regale the animals with tales of his exploits, rubbing the other Fables' noses in his good fortune. Frustration at their restriction to the Farm threatens to become a issue once more! Can the animals find a way out of their situation? Long-time FABLES artist Mark Buckingham takes over writing duties in this concluding volume to the New York Times best-selling series FAIREST"--